Quenching of the relaxation pathway in the Weyl semimetal TaAs - Liu, Jiayun (2021)
Since tantalum arsenide (TaAs) has been experimentally verified as a Weyl semimetal, intensive research has been devoted to study of the unique properties of the material. Despite this, the ultrafast dynamics of TaAs is still not very well understood. In this work, we study the relaxation dynamics in TaAs using transient reflection spectroscopy. From the transient reflection measurement, we observe either a single (fast) or a dual (fast and slow) relaxation, depending on the probing wavelength. The additional relaxation channel is attributed to an asymmetric population of photoexcited electrons and holes.